“PERAN POLRI DALAM PENYIDIKAN TINDAK PIDANA YANG TERKAIT DENGAN MULTI LEVEL MARKETING”. - Ronny Nicolas Sidabutar; Alvi Syahrin; Mahmud Mulyadi; Marlina Marlina (Universitas Sumatera Utara, 2015)
ABSTRACT Business industry Multi Level Marketing (MLM) is a lucrative market society especially with the promised bonuses obtained upon the sale of its products. However, there are also business masquerading as MLM, low quality products but a bonus for members is very large, so as to make the public flocked to follow the program masquerading as MLM business. The issues raised in this study is whether there is legal provision that can ensnare actors masquerading as MLM business practice is, how do I determine the guise of MLM business practices or is actually MLM company that actually benefit from the sale of its products, and how the criminal responsibility of the perpetrators who commit impersonate MLM business practices whether liability or responsibility inpersoon legal entity (legal entity).